Relationship Between GERD-Q Score with Esophagitis Findings in Endoscopy - Billy Siahaan; Arles Arles; Wirhan Azhari (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2020)
Background: Gastro-esophageal Reflux Disease (GERD) is a disease that is commonly found in daily practice and affecting the patients’ quality of life negatively. GERD-Q is a tool in the form of validated questionnaire that is quite useful and easy to use in daily practice to diagnose GERD by symptoms and signs especially in primary care that do not have endoscopy facilities.  This study was built to assess the correlation between GERD-Q score and esophagitis finding in upper gastrointestinal endoscopy in Pekanbaru. Method: This was a prospective cross-sectional study with sample groups of GERD-Q score ≥8 (high GERD-Q score) and GERD-Q score 8 (low GERD-Q score) which underwent upper gastrointestinal endoscopy to assess reflux esophagitis. GERD-Q score data were obtained by direct interview.Results: This study was participated by 65 subjects with reflux esophagitis and 51 non-esophagitis patients that had undergone upper gastrointestinal endoscopy procedure. The 65 subjects with reflux esophagitis were divided into groups based on severity (LA Classification), Grade A 29 subjects (45%), Grade B 23 subjects (35%), Grade C 11 subjects (16%), and Grade D 2 subjects (3%). The result of this study showed that there was a statistically significant correlation between GERD-Q score category with esophagitis findings from upper gastrointestinal endoscopy (p 0.05, PR = 2.6)Conclusion: There is a statistically significant correlation between GERD-Q score and esophagitis findings from endoscopy but no relevance in esophagitis severity.